P115 Quantifying the effect of the COVID-19 pandemic and associated interventions on HIV testing at sexual health services. (16th June 2022) - Tabassum, Tasnuva; Samartsidis, Pantelis; Mohammed, Hamish; Mercer, Catherine H; Field, Nigel; Presanis, Anne; Angelis, Daniela De
Abstract : Introduction: The first COVID-19 lockdown in the UK resulted in disrupted patterns in risk behaviour and access to sexual health services (SHS), and therefore in HIV/STI testing and diagnosis. Methods: To understand how HIV testing was affected by changes in risk behaviour and SHS access, quantification of these two unobserved variables using proxies for each – including number of partners, measures of propensity to consult, number of SHS attendances, and number of HIV and STI tests offered – is necessary. The effects of lockdown on the resulting measures of risk behaviour and SHS access, and of these intermediate variables on the number of HIV tests accepted, can then be estimated. Results: Preliminary results from quantifying SHS access using proxies from GUMCAD surveillance data, including numbers of attendances and HIV/STI tests offered, resulted in a measure of SHS access which corresponds to approximately a unit increase in tests offered and attendances (estimates in range 0.88-1.04). SHS access decreased by 638 units after the lockdown compared to before. The number of HIV tests accepted increased by 0.88 for each unit increase in SHS access. Discussion: These initial findings support the hypothesis that disruption to HIV testing resulted from the lockdown via its effect on SHS access. In ongoing work, we are using data from Natsal-COVID (general population survey), RiiSH-COVID (MSM survey) and the BASHH Clinical Thermometer Survey (SHS staff) to improve our derived measures of risk behaviour and SHS access, and therefore quantify the lockdown effect on HIV/STI testing and diagnosis via each of these paths.